Influência da manipulação da articulação talocrural na estabilidade postural - Paes, Fernando José de Vasconcelos (2011)
Background: The joint manipulation is used to increase joint mobility, decreased muscle tone and pain relief. Nevertheless their use for specific changes in postural stability through force platform in quiet standing posture is very little reported in the literature. Objective: This study assessed the effect of manipulation of the ankle joint in relation to changes stabilometric. Methods: An experimental study consisting of 90 healthy subjects, mean age 22.21 years, height of 1.65 meters, a body mass of 62.58 kg and BMI 22.68 kg / m², divided into three groups (experimental, placebo and control), where a stabilometric evaluation was made with individuals quiet standing on the force platform, it was considered two sensory conditions : with vision and without vision, before and after manipulation of the talocrural joint. The analyzed parameters were area, velocity and median frequency anteroposterior and mediolateral. Results: A significant reduction in the anteroposterior and mediolateral oscillation’ speed on the manipulated group, and there was no such decrease in the placebo and control groups. Conclusions: The talocrural manipulation has the ability to change the parameters of oscillation of the center of pressure in healthy individuals.